The non-linear impacts of poverty, economic growth and unemployment on child abuse - Mohd Shahidan, Shaari; Mujeeb Saif Mohsen, Al Absey; Temitayo B., Majekodunmi; Amri, Sulong; Muhammad Baqir, Abdullah; Abdul Rahim, Ridzuan; K. P. Jaheer, Mukthar (Springer Nature, 2025)
Child abuse remains a persistent and grave issue worldwide, with significant social and economic implications. In Malaysia, despite various measures, child abuse rates have shown a concerning upward trend. Understanding the economic factors that contribute to this issue is essential for crafting effective interventions. This study utilizes the non-linear ARDL method to investigate the relationship between poverty, economic growth, unemployment, and child abuse in Malaysia from 1989 to 2020. The results reveal significant impacts of variations in poverty, economic output, and unemployment on child abuse rates. Specifically, higher unemployment rates are associated with higher child abuse rates over the long term, while lower unemployment rates may lead to lower rates of child abuse. Increases in poverty have been correlated with decreases in child abuse. Both positive and negative fluctuations in economic growth have direct and pronounced effects on the upward trend of child abuse rates. Interestingly, while a positive shock in economic growth increases child abuse, a negative shock mitigates it in the short run. Negative trends in poverty correspond to an increase in abuse rates. These findings highlight the complex relationship between macroeconomic factors and child abuse rates. They underscore the importance of government interventions to address this issue and promote the well-being and happiness of children as the economy advances. Therefore, policymakers are encouraged to prioritize child protection and abuse prevention as interconnected goals. This can be achieved by implementing interventions that address underlying parental stressors, such as offering support for managing work-related stress, reducing the stigma associated with unemployment, and ensuring access to mental health and social support services.